1994
DOI: 10.3109/02841869409098369
|View full text |Cite
|
Sign up to set email alerts
|

Serum Soluble Interleukin-2 Receptor in Colorectal Cancer

Abstract: Preoperative serum soluble interleukin-2 receptor (IL-2R) levels were measured in patients with colorectal cancer, and correlated with various factors as stage, lymph node metastasis, liver metastasis, grade, serum CEA and IAP (immunosuppressive acidic protein). The levels of serum soluble IL-2R in Dukes stage C were significantly higher than in normal control and in Dukes stage A. Serum levels were also significantly higher in patients with lymph node metastasis than in patients without such metastasis, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 16 publications
1
16
0
1
Order By: Relevance
“…High serum concentrations of sIL-2Ra or MMP-9 are correlated with adverse prognosis in patients with colorectal cancer, breast cancer and melanoma [20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…High serum concentrations of sIL-2Ra or MMP-9 are correlated with adverse prognosis in patients with colorectal cancer, breast cancer and melanoma [20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…T lymphocytes activated by IL-2 release a serum soluble form of IL-2R into the bloodstream. High levels of soluble IL-2R were observed in patients with various malignant diseases, autoimmune disorders, infections and many other inflammatory diseases [2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 18, 19, 20, 21]. There are some reports regarding the levels of IL-2R in patients with gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…1). Increased levels of serum soluble IL-2R have been found in patients with diverse diseases including lymphoma [2], lung cancer [3], gastrointestinal cancer [4, 5, 6, 7, 8], breast cancer [9], autoimmune diseases [10, 11, 12], infections [13, 14]and organ allograft rejection [15], for example. We have already reported increased concentrations of serum soluble IL-2R in patients with gastric cancer [4].…”
Section: Introductionmentioning
confidence: 99%
“…Similar studies in various solid tumor cases have also shown sIL-2R to be an adverse prognostic feature, especially in patients with nasopharyngeal cancer [34,35], colorectal cancer [36,37], breast cancer [38], ovarian cancer [39][40][41], gastric cancer [42,43], lung cancer [44,45] and leukemia [46,47], respectively. IL-2 has been introduced as a cancer treatment since 1992.…”
Section: Interleukinmentioning
confidence: 99%